The unique ligand binding features of subfamily-II iLBPs with respect to bile salts and related drugs. (April 2015) - Favretto, Filippo; Ceccon, Alberto; Zanzoni, Serena; D'Onofrio, Mariapina; Ragona, Laura; Molinari, Henriette; Assfalg, Michael
Abstract: Intracellular lipid binding proteins (iLBPs) are a family of evolutionarily related small cytoplasmic proteins implicated in the transcellular transport of lipophilic ligands. Subfamily-II iLBPs include the liver fatty acid binding protein (L-FABP), and the ileal and the liver and ileal bile acid binding proteins (L-BABP and I-BABP). Atomic-level investigations during the past 15–20 years have delivered relevant information on bile acid binding by this protein group, revealing unique features including binding cooperativity, promiscuity, and site selectivity. Using NMR spectroscopy and other biophysical techniques, our laboratories have contributed to an understanding of the molecular determinants of some of these properties and their generality among proteins from different animal species. We focused especially on formation of heterotypic complexes, considering the mixed compositions of physiological bile acid pools. Experiments performed with synthetic bile acid derivatives showed that iLBPs could act as targets for cell-specific contrast agents and, more generally, as effective carriers of amphiphilic drugs. This review collects the major findings related to bile salt interactions with iLBPs aiming to provide keys for a deeper understanding of protein-mediated intracellular bile salt trafficking.